A study on the relationship between emotional intelligence and life satisfaction at Permodalan Nasional Berhad Kuala Lumpur / Siti Nurhidayah Ibrahim - Ibrahim, Siti Nurhidayah (Faculty of Business and Management, 2019)
The purpose of this research finding were conducted is to evaluate and analyzed the relationship between emotional intelligence toward life satisfaction. The researcher decided the emotional intelligence as independent variable and life satisfaction as dependent variable to conduct this finding. The emotional intelligence are consisted with three component which is social support, self-esteem and perceived stress in order to identified the factor that influence the life satisfaction at selected organization. Emotional intelligence was define as described as individual's judgment as entire, despite the emotions and feel that are faced in the situation (Champoo, 2015). Both of this variables are connected and affected to one another. The objective of this study is to identify what are the component of emotional intelligence, which component of emotional intelligence contribute highest and lowest influence toward life satisfaction and to investigate the relationship between emotional intelligence and life satisfaction. The researcher decided to conducted this finding at Permodalan Nasional Berhad in order to find which component that influence life satisfaction among the employees. In order to collect the data of the respondents, the researcher prepared and distributed the questionnaire at the selected department. The data obtained were analyzed by using Statistical Package in Sciences Social Software (SPSS). From the result obtained, the researcher also come up with clear explanation about the finding, recommendation and suggestion for future study in order to have the better research finding.